The Relationship between Bullying and Mental Health in Adolescents at SMP Negeri 2 Air Putih Indrapura in 2024 - Lili Tumanggor; Friska Ginting P; Agustina Devi Yanti Pardede (Pusat riset dan Inovasi Nasional, 2025)
Introduction : Bullying is aggressive behavior carried out by a person or group of people against another person or group of people who are weaker. Mental Health is a problem with emotional development, behavior and development. The aim of the research is to determine the relationship between bullying and mental health among teenagers. This research uses a quantitative research design. The research method used was cross sectional. The sampling technique in this research uses random sampling with the number of respondents are 159 people. The instrument used is questionnaire sheet. This study uses Independent variable Bullying and dependent variable mental health. Data analysis in this study uses the chi-square test. The results of this study show that there is bullying behavior as many as (82.4%) and mental health was in the disturbed category as many as 129 respondents (81.1%). The statistical test results are obtained with a p-value of 0.000, a value >5. These results indicate that there is a significant relationship between bullying and mental health for respondents. It is necessary for students to respect each other without looking at their background, physique or any differences to be good friends, get along well, support each other, provide assistance and try not to bully weak friends and the school is expected to pay more attention to bullying actions that occur in school environment.